مهارات إدارة الصف وعلاقتها بجودة التكوين لدى المعلمين الجدد بالطور الإبتدائي خريجي المدارس العليا - (:unkn) unknown (جامعة البليدة 2؛ كلية العلوم الانسانية والاجتماعية, 2024)
تهدف الدارسة إلى التعرف على العلاقة بين مهاارت إدارة الصف وجودة التكوين لدى كما سعت الدارسة إلى ، المعلمين الجدد خريجي المدارس العليا بالتعليم الإبتدائي معرفة الفروق الموجودة في مهاارت إدارة الصف حسب متغير الخبرة بالنسبة للمعلمين الجدد خريجي المدارس العليا وقد أجريت الدارسة بالمدارس الإبتدائية أستاذ وأستاذة 80 التابعة لولاية عين الدفلى حيث تم التطبيق على عينة قوامها خريجي المدارس العليا بالتعليم الإبتدائي الجدد . كما إستخدمت في دارستها إستبيانين ، واعتمدت الباحثة على المنهج الوصفي حيث 2016 للقياس حيث تم بناء المقياس الأول من قبل الباحث رمضانية أحمد والثاني مقياس ، بندا مقسمة على خمسة محاور 50 يحتوي هذا الأخير على . 2019 مهاارت إدارة الصف للباحث ميازيني الجيلالي وقد تم التحقق من صدقهما وثباتهما وكشفت النتائج عن تمتعهم بمعاملات عالية من ) )حزمة SPSS وتمت المعالجة الإحصائية للبيانات بنظام ، الصدق والثبات الإحصاء بالعلوم الإجتماعية وكانت النتائج المتحصل عليها كالآتي : . وجود علاقة إرتباطية دالة بين مهاارت إدارة الصف وجودة التكوين  وجود  مستوى عال من جودة التكوين بالمدارس العليا للأساتذة . وجود  مستوى مرتفع لمهاارت إدارة الصف للمعلمين الجدد خريجي المدارس العليا . وجود  فروق في مهاارت إدارة الصف تعزى إلى متغير سنوات الخبرة . في ضوء هذه النتائج لوحظ تحقق فرضيات الدارسة وتبقى نتائج الدارسة في إطار حدودها البشرية والزمانية والمكانية والأداتيية ط summary The study aims to identify the relationship between classroom management skills and the quality of formation of new teachers, graduates of high schools in primary education. The study also sought to know the differences in class management skills according to the variable of experience for new teachers graduates of high schools. Where it was applied to a sample of 80 professors and new graduates of high schools in primary education . The researcher relied on the descriptive approach, and in her study she used two questionnaires for measurement, where the first scale was built by the researcher Ramadania Ahmed 2016, as the latter contains 50 items divided into five axes ,and the second scale is the class management skills scale of the researcher Mezaini Al-Jilali 2019. Their validity and reliability were verified, and the results revealed that they enjoyed high coefficients of honesty and reliability. The statistical processing of the data was carried out using the SPSS system (Statistics Package in Social Sciences). The obtained results were as follows: •The existence of a significant correlation between classroom management skills and the quality of training. •The existence of a high level of quality training in higher schools for teachers. •A high level of classroom management skills for new teachers, graduates of high schools. • There are differences in classroom management skills due to the variable years of experience. In the light of these results, it was noted that the hypotheses of the study were achieved, and the results of the study remain within the framework of its human ,temporal, spatial, and instrumental limits.
دراسة ميدانية بمدارس ولاية عين الدفلى
Keywords: ادارة الصف; المعلمين